Sexual Dating Aggression Across Grades 8 Through 12: Timing and Predictors of Onset - Reyes, H. Luz McNaughton (2012)
Investigators have identified a number of factors that increase risk for physical and psychological dating abuse perpetration during adolescence, but as yet little is known about the etiology of sexual dating aggression during this critical developmental period. This is an important gap in the literature given that research suggests that patterns of sexual dating violence that are established during this period may carry over into young adulthood. Using a sample of 459 male adolescents (76% White, 19% Black), the current study used survival analysis to examine the timing and predictors of sexual dating aggression perpetration onset across grades 8 through 12. Risk for sexual dating aggression onset increased across early adolescence, peaked in the 10(th) grade, and desisted thereafter. As predicted based on the Confluence Model of sexual aggression, associations between early physical aggression towards peers and dates and sexual aggression onset were stronger for teens reporting higher levels of rape myth acceptance. Contrary to predictions, inter-parental violence, prior victimization experiences, and parental monitoring knowledge did not predict sexual dating aggression onset. Findings support the notion that risk factors may work synergistically to predict sexual dating aggression and highlight the importance of rape myth acceptance as a construct that should be addressed by violence prevention programs.